SOME TRENDS IN INFORMATION SUPPORT OF NATIONAL CULTURAL AND ETHNORELIGIOUS SELF-DETERMINATION ADHYGE-ABKHAZ AND TURKIC PEOPLES OF THE NORTH CAUCASUS AND CRIMEA - Gennady Vladimirovich Kossov (Современная наука и инновации)
In the article, based on the analysis of more than 300 articles posted in the Internet resources of the North Caucasus Federal District and the Crimea during the first half of 2017, the main topics are highlighted in covering the problems of ethnic-cultural and ethno-religious self-determination of the Adyg-Abkhaz and Turkic peoples of the North Caucasus and Crimea. Denomination points are identified, proposals for optimization of managerial processes in the regions are formulated.